Fluctuations of rest and activity periods in the intermittent growth of rubber tree nursery seedlings - Cid, Luis Pedro Barrueto (Pesquisa Agropecuaria Brasileira, 2014)
In nursery rubber tree seedlings the periods of rest and growth activity of new flushes were determined by measuring the flush length. There was no synchronization in the outcome of apical meristem activity, so that plants in the leaflet stage B (anthocyanin rich red leaflets) were found individually at different time. This fact renders difficult the chemical control of leaf diseases and pests in nurseries such as South American Leaf Blight caused by Microcyclus ulei and the leaf-eater caterpillar (Erinnyis ello).